Perception and Experiences of Undergraduate Nursing Students on Clinical Learning Environment in a Public University - Mabel D Rozario; Delowara Begum; Noopur D. Costa; Most Nasrin; Hasina Akter (Dubai Medical Journal)
Background: Clinical learning is viewed as a fundamental and essential part of nursing education. Clinical training offers chances to use the theoretical knowledge in practice, raise problem-solving and executive skills, learn time management, collaborate with others, and develop professionalism. Objective: This study intended to reveal the perceptions and experiences of the clinical learning environment of undergraduate nursing students and the influencing factors of the clinical learning process. Methodology: A mixed-method approach comprising qualitative, exploratory, and phenomenological research design was used. Nonprobability purposive sampling technique was applied to select the sample. Data were collected by mixed methods of inquiries of 14 in-depth interviews, 4 focus group discussions, and clinical observations from third- and fourth-year bachelor of nursing students. A content analysis approach was used to analyze the collected contents. Results: The study identified seven factors influencing nursing students’ clinical learning experience. An expert clinical instructor, supportive role of clinical nurses, reliable communication and relationship, job description, theory-practice integration, availability of resources, and social and psychological factors are essential for effective clinical learning. Conclusion: Nursing students face many challenges in the clinical learning environment. For effective clinical learning, the seven identified factors are recommended to consider while designing clinical learning instruments for the students.